Influence of Principals’ Involvement of Students in Decision Making on Discipline in Secondary Schools, Kenya - Wambua, Patrick; okoth, Ursula A.; Kalai, Jeremiah M. (European Scientific Journal, ESJ, 2017)
Stakeholder involvement is critical in that it can enhance levels of ownership of the decisions made as well building trust between the governors and the governed. The purpose of the study was to investigate the influence principals’ involvement of students in decision making on student discipline in secondary schools, Kenya. The study sought to establish the areas of student involvement in decision making by secondary school principals and determine whether significant differences exist between reported incidences of student indiscipline based on the levels of student involvement in decision making in secondary schools. The study employed systems theory by Ludwig Bertalanffy which looks at organisations as systems. Schools are viewed as parts joined together by web of relationships both within and outside the school. Using a descriptive survey design with a target population of 354 secondary school principals, 300 teachers and 4602 student leaders, a sample of 118 principals and 1534 student leaders were sampled through stratified proportionate sampling. Questionnaires for principals and student leaders were used for the study. The return rate was 101 principals (85.6%) and 1433(93.4%) student leaders. Cross-tabulations were done to determine whether the mean occurrences of student indiscipline were different based on levels of principals’ involvement of students in decision making. The findings indicated that 94.1 per cent of principals involved students in decision making with varying degrees of involvement for student welfare. Analysis of Variance (ANOVA) did not indicate significant differences between involvement in decision making and lowering of cases of drug and substance abuse, cases of arson and student suspension. The incidences of student indiscipline in those schools were low, as evidenced by lowered cases of arson factor that could be attributed to students sense of ownership and feeling respected and recognised. The study concluded that involvement in decision making is a key driver to student’s discipline. The study could be replicated in a number of counties involving teachers and Board members as respondents. In addition, the study could be replicated using mixed methods with more inclination to the qualitative research.